Childhood Idiopathic Thrombocytopenic Purpura: A Retrospective Analysis Of Clinical Features And Response To Treatment - Abbas, Sawsan S. (Journal of the Faculty of Medicine Baghdad, 2006)
Background : A retrospective study was done in the Pediatric ward /AL-Kadhimiyia Teaching Hospital on cases diagnosed as idiopathic thrombocytopenic Purpura admitted since the first of January1992 – the end of December 2004.Aim of the study : The objective of this paper is to review the natural history of idiopathic thrombocytopenic Purpura , presenting feature and response to treatment.Patients and methods : The review included age ,sex , clinical presentation , physical finding , complications , investigation ,treatment and course of the diseases .Results: total number of the patients were 65, peak age was between (2 -5) years, 40 cases (61.53%). Females were affected more than Males with male: female ratio of 1: 2.09 .There was no seasonal variation and all of the cases were preceded by viral upper respiratory tract infection .The main presentation was petechiae and ecchymosis, were found in all of them (100%) followed by epistaxis, 43 cases (66.15 %). In the majority the platelet count was < 20.000 X 10 9 /L, 32 cases (49.23 %) and the hemoglobin level was between 10 – 11gm /dl in most of them, 43 cases (66.15%). Steroid was the first line treatment, response occur within 2 – 3 weeks in the majority, 51 cases (78.46%). Chronic idiopathic thrombocytopenic Purpura occurred in 3 cases only (4.61%).Splenectomy was done in 2 of them (66.66%). No mortality detected.Conclusion : Idiopathic thrombocytopenic purpura is a mild disease with complete recovery in the majority of patients